2021
DOI: 10.1002/oby.23154
|View full text |Cite
|
Sign up to set email alerts
|

Weight Can’t Wait: A Guide to Discussing Obesity and Organizing Treatment in the Primary Care Setting

Abstract: ObjectiveThe objective of this study was to develop a simple and practical guide for discussing and managing obesity in primary care settings.MethodsThis study convened representatives from 12 primary care and obesity specialty organizations for a series of roundtable meetings to discuss the key components of obesity treatment in primary care. Attendees identified the need for a guide for primary care providers that outlined the key steps for discussing obesity with patients and managing their care while recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Weight loss discussions should follow an approach such as that outlined by the Strategies to Overcome and Prevent Obesity Alliance toolkit. 99 Intentional weight loss should be a therapeutic goal among individuals with obesity and prevalent CVD. Moderate intentional weight loss (5%-10%) should be targeted to improve metabolic risk factor control among patients with CVD and to improve functional status and quality of life in patients with HF.…”
Section: Obesity Mets and Cvdmentioning
confidence: 99%
“…Weight loss discussions should follow an approach such as that outlined by the Strategies to Overcome and Prevent Obesity Alliance toolkit. 99 Intentional weight loss should be a therapeutic goal among individuals with obesity and prevalent CVD. Moderate intentional weight loss (5%-10%) should be targeted to improve metabolic risk factor control among patients with CVD and to improve functional status and quality of life in patients with HF.…”
Section: Obesity Mets and Cvdmentioning
confidence: 99%
“…One example is called the "6A Framework," which provides a word-by-word script to engage with the patient and develop a shared decision-making weight loss plan. 28 Opportunity can be addressed by creating aids to help providers access anthropometric data on the electronic medical record (BMI flag) and create a streamlined referral process to a weight management program. A quality improvement intervention by Wang'ondu et al 29 demonstrated that educating providers on how to access weight and BMI from the medical record quickly increased documentation of obesity from 46% to 79%.…”
Section: Discussionmentioning
confidence: 99%
“…One example is called the “6A Framework,” which provides a word-by-word script to engage with the patient and develop a shared decision-making weight loss plan. 28…”
Section: Discussionmentioning
confidence: 99%
“…A patient-centered and nonjudgmental approach to initiating the weight loss discussion is most effective, 127 with the STOP Obesity Alliance toolkit serving as a useful framework for clinicians. 128 Weight loss through lifestyle modification is linked to improved risk factor control among patients with obesity and ASCVD. 129 In patients with obesity and HFpEF, lifestyle modification, including exercise training, improves functional status.…”
Section: Obesity Mets Components and Cvdmentioning
confidence: 99%